Development of Flashcard Media Assisted by the SAS Method for Early Reading Teaching in Elementary Schools - Azzahra, Salsabila; Rini, Titis Angga; Muzaki, Ferril Irham (Universitas Negeri Malang, 2024)
Researchers conducted research using observation techniques and interviews with grade 1 teachers of SDN Mandaranrejo 1 Pasuruan City, found 15 students whose reading skills were still classified as low. Flashcard media assisted by the SAS method was made with the aim of improving reading skills at an early stage aimed at low grades. Researchers developed learning media for early reading learning activities in the form of cards that include examples of words and sentences based on the SAS method along with images that can be interesting. This research and development aims to develop a product in the form of Flashcard media for beginning reading that is valid according to experts, namely material experts, media experts, and users, namely teachers and students. This research uses the R&D (Research and Development) research method of the ADDIE model which consists of 5 stages. This research and development obtained validation results by material experts of 97% and validation by media experts of 100%. While the results of user validation by teachers obtained 100% and by students at 98% so that Flashcard media assisted by the SAS method was included in the criteria very valid and interesting according to material experts, media experts, and users. Therefore, Flashcard media can be used for learning beginning reading. Keywords: Flashcards; SAS Method; Beginning Reading